FAKTOR-FAKTOR YANG MEMENGARUHI CAPITAL STRUCTURE DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Grace Monica Kionggo; Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2022)
This study was done to examine the effects of asset structure, liquidity, profitability, and business risk on capital structure and whether firm size is able to moderate the effects of asset structure, liquidity and profitability on capital structure. The subject of this study was 202 manufacturing companies listed in the Indonesia Stock Exchange and purposive sampling was used to narrow the samples down to 59 companies. The data used was from the 2017-2020 period and Eviews 12 was used to process said data. Results show that asset structure and profitability negatively does not affect capital structure, liquidity positively affects capital structure and business risk positively does not affect capital structure. Firm size was proven to be able to moderate the effects of liquidity, but was unable to moderate the effects of asset structure and profitability on capital structure.